2022
DOI: 10.1097/cmr.0000000000000826
|View full text |Cite
|
Sign up to set email alerts
|

Female melanoma and estrogen receptors expression: an immunohistochemical pilot study

Abstract: Epidemiologic data highlight sex differences in melanoma outcome. A putative role of sex hormones is still under investigation. Very few laboratory investigations have focused on the level of expression of estrogen receptors in melanoma. We evaluated the presence of estrogen receptors alpha (ERα) and beta (ERβ) in melanoma specimens from female patients with a previous history of breast carcinoma (BC). Moreover, another group of female patients undergoing ovarian stimulation (OS) were also compared to two cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…It is possible that the peculiar role of sex hormones (androgen and estrogen) in the development of melanomas, as well as the complex intracellular mechanisms regulated by these 2 molecules, could explain the different PRAME expression observed in females and males. 45,46 To conclude, the data here obtained indicate that PRAME is a useful tool for the…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It is possible that the peculiar role of sex hormones (androgen and estrogen) in the development of melanomas, as well as the complex intracellular mechanisms regulated by these 2 molecules, could explain the different PRAME expression observed in females and males. 45,46 To conclude, the data here obtained indicate that PRAME is a useful tool for the…”
Section: Discussionsupporting
confidence: 54%
“…It is possible that the peculiar role of sex hormones (androgen and estrogen) in the development of melanomas, as well as the complex intracellular mechanisms regulated by these 2 molecules, could explain the different PRAME expression observed in females and males. 45 , 46 To conclude, the data here obtained indicate that PRAME is a useful tool for the appropriate diagnosis of MBML-H&N and MM-H&N. The most reliable score to differentiate MM-H&N and MBML-H&N is that proposed by Raghavan and colleagues (< 60% vs. ≥60% of PRAME-positive cells), but a subgroup of specifically sited MM-H&N (palate) can be PRAME-negative (although this assumption is based on a low number of cases and future studies are needed to verify this finding). High PRAME expression (≥60%) was found in association with specific mucosal sites, nodular histotype, and female sex, suggesting a distinct involvement of this molecule in the pathogenesis of these subgroups of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Sex hormone receptor expression is induced during pregnancy or while using oral contraceptives, which may increase the risk of melanoma development and may be associated with pigment changes in melanoma precursor lesions (5). However, the association between hormone receptor expression and melanoma development is cont-radictory (6)(7)(8)(9)(10). Recent studies investigating G protein-coupled oestrogen receptor (GPER) on cultured melanoma cells have shown that selective GPER activation induced long-term changes that maintained a more differentiated cell state, increased pigment production, decreased proliferative capacity, and decreased expression of the onco-driver and stem cell marker c-Myc (11).…”
Section: Discussionmentioning
confidence: 99%
“…Despite potential menin involvement in the development of melanoma, germline MEN1 mutations are not prone to this malignancy, as, for instance, has been found with other genes such as CDKN2A [ 93 , 126 , 127 ]. Other hormonal dysfunctions involving growth factors, growth hormone–IGF-1 axes, or estrogens/estrogen receptor status have been reported in melanoma without a clear connection to endocrine tumors underlying MEN1 [ 128 , 129 , 130 , 131 , 132 , 133 ]. Larger clinical studies on MEN1 and potential skin involvement are necessary, including longitudinal data and comparison with patients without dermatological issues.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the present topic of following the skin tumors in MEN1 represents a fraction of a more complex picture that includes cutaneous aspects in association with various tumor-related hormonal issues as seen in acromegaly, primary hyperparathyroidism, or similar findings in pancreatic NETs in addition to heterogeneous anomalies in MEN2 syndrome (involving both MEN2A and MEN2B type, such as dermal hyperneury, cutaneous lichen amyloidosis, sclerotic fibromas, atypical rash, macular amyloidosis, etc. ), but also, clinical expression of carcinoid syndrome caused by gastroenteropancreatic NETs or metastatic medullary thyroid cancer [ 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ]. A good dermatological—endocrinological collaboration is required to benefit our patients.…”
Section: Discussionmentioning
confidence: 99%